Pengaruh Inovasi Terhadap Performa Usaha Melalui Keunggulan Bersaing Pada UMKM Syariah di Kota Semarang - Laura Fabiola Soegihono; Ahyar Yuniawan (ITB AAS INDONESIA Surakarta, 2023)
Business performance is an assessment of how the strategy implemented by the company is realized. By assessing business performance, it can be seen how far the company has developed. The aim of this research is to find out whether innovation has an effect on business performance, and to find out whether competitive advantage is able to mediate innovation on business performance. The population in this research are MSMEs in Semarang City who have been established for more than 5 years. The number of samples in this study was 115 respondents using a cluster sampling technique. Data collection techniques use questionnaires and observation methods. The data analysis method uses multiple linear regression with a path analysis approach and the SPSS program. The research results show that the innovation variable has an influence on business performance, then competitive advantage also has a positive and significant influence on business performance. The results of the indirect effect test also show that competitive advantage is able to mediate the relationship between innovation and business performance. The implementation of innovation strategies influences the business performance of MSMEs in Semarang City. Competitive advantage also influences business performance and can mediate the relationship between innovation and the business performance of MSMEs in Semarang City. Suggestions for MSME players in Semarang City to implement innovation strategies that are appropriate to the business sector they are undertaking so that they will increase their competitive advantage which will improve business performance.